2021
DOI: 10.1088/1475-7516/2021/03/063
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde polish doughnuts around boson stars

Abstract: We investigate polish doughnuts with a uniform constant specific angular momentum distribution in the space-times of rotating boson stars. In such space-times thick tori can exhibit unique features not present in Kerr space-times. For instance, in the context of retrograde tori, they may possess two centers connected or not by a cusp. Rotating boson stars also feature a static ring, neither present in Kerr space-times. This static ring consists of static orbits, where particles are at rest with respect to a ze… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 64 publications
(125 reference statements)
1
6
0
Order By: Relevance
“…Thus, a particle could sit at rest right at the center. Also bound oscillating motion across the center is possible, as observed also in other regular spacetimes [87]. In Figs.…”
Section: Particle Motionsupporting
confidence: 69%
“…Thus, a particle could sit at rest right at the center. Also bound oscillating motion across the center is possible, as observed also in other regular spacetimes [87]. In Figs.…”
Section: Particle Motionsupporting
confidence: 69%
“…As shown in [19], spacetimes endowed with static orbits [36] can shelter static surfaces in the context of thick tori. While static orbits are circular geodesics in the equatorial plane, for which a particle remains static with respect to the ZAMO, static surfaces are their generalization for fluids.…”
Section: Constant Specific Angular Momentum Polish Doughnutsmentioning
confidence: 99%
“…GRMHD simulations with a similar setup are also used to address advection-dominated flows, the evolution of weakly magnetized disks, jet formation and the differences between possible images of black holes and boson stars (BS) [7,8,9,10,11,12]. Outside the context of GRMHD simulations, Polish doughnuts are also used to address possible tori geometries around exotic spacetimes such as Kerrde Sitter backgrounds, distorted static BHs, deformed compact objects, Kehagias-Sfetsos naked singularities and BSs [13,14,15,16,17,18,19]. Although some models of doughnuts may include magnetic fields and non-constant specific angular momentum distribution, the constant specific angular momentum case remains being an important first step in this field of research, since in this case the torus solutions are marginally stable for Kerr BHs and hold similar topologies as the ones found for different specific angular momentum distributions [20,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [77], the authors explored the Kα iron line of a sample of three quite different solutions of KBHsSH to see if they could, as a template, fit the fabricated data produced by a Kerr BH and found that two of them performed well enough to be dismissed. Thick tori (a generalization of the Polish Doughnut) have also been constructed for KBHsSH [78] and BSs [48,79], which can be used as initial data for dynamical simulations as well as for modeling the imaging of a dark compact object. Dynamical simulations of accreting disks and disruption events around BSs in comparison to BHS have been considered in [80,81], while the possibility of constraining the gravitational theory and object via our current imaging capacities is the subject of study in [82].…”
Section: Introductionmentioning
confidence: 99%